The Effectiveness of Psychoeducational Intervention in Reducing FoMO and Enhancing Positive Self-Concept among Junior High School Students - Hanifah, Fikrotul; Harianti, Winda Sri; Azkia, Muhammad Ajmal; Rahman, Nur Aditya; Kristiani, Damai Dian; Salma, Nailah Rizkiyanti; Revalina, Euveline Naftalianda (Universitas Negeri Surabaya, 2025)
Background: Fear of Missing Out (FoMO) is a prevalent psychological phenomenon among adolescents in the digital era, driven by social media exposure and low self-concept. Objective: This study aims to evaluate the effectiveness of a psychoeducational intervention designed to strengthen positive self-concept as a preventive measure against FoMO in junior high school students. Method: The research employed a quasi-experimental one-group pre-test and post-test design involving 22 students from SMP Bukit Aksara, Semarang, of whom 20 completed the entire intervention. The instruments used were the FoMO Scale and a Self-Concept Knowledge Test. Results: The results from the paired sample t-test showed a statistically significant reduction in FoMO scores (p = 0.015). Qualitative analysis of open-ended responses and reflective journals indicated improved emotional awareness and self-acceptance, although cognitive understanding of self-concept remained inconsistent. Conclusion: The psychoeducational program effectively reduced FoMO tendencies and enhanced reflective and emotional capacities in participants, though cognitive outcomes require further instructional refinement. Abstrak Latar Belakang: Fear of Missing Out (FoMO) merupakan fenomena psikologis yang banyak dialami remaja, terutama dalam konteks penggunaan media sosial yang berlebihan. Remaja dengan konsep diri yang rendah lebih rentan terhadap kecemasan, tekanan teman sebaya, dan perilaku daring kompulsif. Tujuan: Penelitian ini bertujuan untuk mengevaluasi efektivitas intervensi psikoedukatif terstruktur dalam menurunkan kecenderungan FoMO pada siswa sekolah menengah pertama. Metode: Penelitian ini menggunakan desain kuasi-eksperimen dengan model one-group pre-test and post-test. Sebanyak 20 siswa dari SMP Bukit Aksara mengikuti intervensi. Data dikumpulkan menggunakan Skala FoMO yang telah diadaptasi ke dalam Bahasa Indonesia dan dianalisis dengan statistik deskriptif serta uji t berpasangan. Hasil: Analisis menunjukkan penurunan skor FoMO yang signifikan secara statistik antara pre-test dan post-test (p = 0,015). Mayoritas peserta berpindah dari kategori FoMO sedang–tinggi ke tingkat yang lebih rendah setelah intervensi. Kesimpulan: Program psikoedukatif terbukti efektif dalam menurunkan kecenderungan FoMO pada remaja. Penelitian ini memberikan kontribusi berupa model intervensi praktis berbasis psikoedukasi kelompok yang terstruktur dan aktif untuk menangani kecemasan terkait media sosial pada siswa sekolah menengah pertama.